2022
DOI: 10.1016/j.vacun.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictive demographic factors of Covid-19 vaccine hesitancy in Venezuela: A cross-sectional study

Abstract: Objetivo: Evaluar si siete variables demográficas (edad, género, religión, origen étnico, ingresos, nivel educativo y opiniones políticas) son predictivas del rechazo a la vacuna del Covid-19. Material y métodos: 327 participantes completaron una encuesta con preguntas sobre cada una de las variables. Resultados: la edad, el género y las opiniones políticas no tienen una correlación estadísticamente significativa con el rechazo la vacuna. El origen étnico y la religión predicen el rechazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Also, a study in Russia showed that older people and those with a lower level of education were more reluctant against vaccination [14]. While the participants in the present study did not relate ethnicity or religion to their vaccination refusal, a study in Venezuela on 327 participants showed that the most common reasons for hesitancy against COVID-19 vaccination were ethnicity and religion, whereas income and educational attainment had weak and moderate negative correlations with hesitancy, respectively [15].…”
Section: Discussioncontrasting
confidence: 67%
“…Also, a study in Russia showed that older people and those with a lower level of education were more reluctant against vaccination [14]. While the participants in the present study did not relate ethnicity or religion to their vaccination refusal, a study in Venezuela on 327 participants showed that the most common reasons for hesitancy against COVID-19 vaccination were ethnicity and religion, whereas income and educational attainment had weak and moderate negative correlations with hesitancy, respectively [15].…”
Section: Discussioncontrasting
confidence: 67%
“…Interestingly, Protestant religious affiliation was associated with a lower intention to accept the vaccine, studies in the South American context such as Venezuela presented similar results. 47 This may be attributed to a lower perceived risk by members of these churches, due to religious values or media influence and social ties that form personalized attitudes toward science, the risks associated with vaccines, and trust in the health care system. 48 , 49 In comparison with Catholics, Peru presents a model of Church-State relations that coordinates and promotes the relations between the executive branch and the church, supporting the measures taken by the government, providing a better response despite the freedom of worship.…”
Section: Discussionmentioning
confidence: 99%
“…Willingness to receive vaccines against SARS-CoV-2 varied depending on the studied population and ranged from ~70% in a general UK population to over 90% in German healthcare workers [4]. Vaccine hesitancy may be influenced by sociodemographic factors, such as educational level, income, or geographic region [5,6]. By ongoing surveillance and evaluation of adverse event reporting, health authorities nevertheless recommend continuing vaccination programs to achieve herd immunity [7].…”
Section: Introductionmentioning
confidence: 99%